2010
DOI: 10.1089/jpm.2010.0209
|View full text |Cite
|
Sign up to set email alerts
|

Geographic Access to Hospice in the United States

Abstract: Recent growth in the hospice industry has resulted in widespread geographic access to hospice care in the United States, although state and community level variation exists. Future research regarding variation and disparities in hospice use should focus on barriers other than geographic proximity to a hospice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
56
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(58 citation statements)
references
References 24 publications
2
56
0
Order By: Relevance
“…27 Another review focused on GIP care claims highly vulnerable to fraud; one such type was GIP care of seven or more days in a monthly billing period; this edit reported a denial rate of nearly 62%. 28 Armed with these audit results, the CMS has made it clear to hospice providers that care can be billed at the GIP level in the event of imminent death, a direct discharge from a hospital to a hospice, or a caregiver breakdown, but only when the hospice provider can provide the documentation supporting a need for aggressive pain/symptom management. Hospice care billed previously as GIP care is now strictly reimbursed only at the routine care rate or respite care rate—leading to a considerable reduction in payments.…”
Section: Discussionmentioning
confidence: 99%
“…27 Another review focused on GIP care claims highly vulnerable to fraud; one such type was GIP care of seven or more days in a monthly billing period; this edit reported a denial rate of nearly 62%. 28 Armed with these audit results, the CMS has made it clear to hospice providers that care can be billed at the GIP level in the event of imminent death, a direct discharge from a hospital to a hospice, or a caregiver breakdown, but only when the hospice provider can provide the documentation supporting a need for aggressive pain/symptom management. Hospice care billed previously as GIP care is now strictly reimbursed only at the routine care rate or respite care rate—leading to a considerable reduction in payments.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, Carlson and colleagues used 2008 Medicare data to estimate the proportion of the U.S. population living within 30 and 60 minutes driving time of a hospice. 13 The researchers showed that 88% of the population lived in a community within 30 minutes and 98% lived in a community within 60 minutes of a hospice. The literature suggests that the recent growth in the hospice industry may have resulted in widespread geographic access to hospice care in the United States.…”
mentioning
confidence: 99%
“…This may be due not only to an increase in availability and accessibility of hospice but also to its acceptability among African Americans as a result of initiatives to address potential barriers to hospice use. [1][2][3][4][5][6][7][8] The most commonly cited barriers to hospice use for African Americans include preferences for life-sustaining therapies, lack of knowledge about hospice, mistrust of the health care system, and spiritual beliefs. [9][10][11][12][13][14] Experts and national organizations have identified a role for individual hospice providers in addressing some of these barriers.…”
Section: Introductionmentioning
confidence: 99%